Financial inclusion and natural resource rents: non-linear effects on economic growth in Sub-Saharan Africa - Madouri, Abderazak; Tidjani, Chemseddine (Frontiers in Applied Mathematics and Statistics, 2026)
This study investigates the relationship between financial inclusion, natural resource rents, and economic growth across 21 Sub-Saharan African countries from 2014 to 2022. It employs the System Generalized Method of Moments (System GMM) alongside Panel Quantile-on-Quantile Regression (Panel QQR). The analysis uncovers robust non-linear dynamics and distributional heterogeneities. The SGMM results robustly confirm a statistically significant U-shaped relationship, whereby financial inclusion initially impedes economic growth but subsequently fosters it—under various interactions that exert positive and significant influences on performance. These findings underscore that achieving sustainable growth and circumventing the resource curse is conditional upon the effective moderating role of governance in concert with the contribution of financial inclusion. The QQR results reveal a nuanced landscape: financial inclusion exerts its strongest positive effects at the mid-level quantiles of the growth distribution, while it exhibits adverse impacts at the extreme lower and upper tails—reflecting the dual threats of financial exclusion and excessive inclusion. Similarly, natural resource rents show a negative association with growth at lower quantiles, which supports the resource curse hypothesis; however, they enhance growth at higher quantiles, in line with stronger governance capacity and institutional reforms. Governance consistently exerts a positive and intensifying influence across all quantiles, reinforcing its essential role in promoting sustainable economic development. These insights underscore the urgency of implementing finely tuned, context-sensitive financial inclusion strategies alongside transparent and accountable resource revenue management. The study concludes with actionable policy recommendations aligned with key Sustainable Development Goals (SDGs) and a resilient growth trajectory across the region.